2020
DOI: 10.3389/fmech.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Strain Hardening From Elastic-Perfectly Plastic to Perfectly Elastic Indentation Single Asperity Contact

Abstract: Indentation measurements are a crucial technique for measuring mechanical properties. Although several contact models have been developed to relate force-displacement measurements with the mechanical properties, they all consider simplifying assumptions, such as no strain hardening, which significantly affects the predictions. In this study, the effect of bilinear strain hardening on the contact parameters for indentations is investigated. Simulations show that even 1% strain hardening causes significant chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The plane section assumption: After bending, the blank cross section, which is perpendicular to the fiber, is still a plane (Boisse et al , 2018). The material is elastic-perfectly plastic material, so there is no strain hardening while deforming (Ghaednia et al , 2020). The TA is in the inner bending arc (Zhu et al , 2007).…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The plane section assumption: After bending, the blank cross section, which is perpendicular to the fiber, is still a plane (Boisse et al , 2018). The material is elastic-perfectly plastic material, so there is no strain hardening while deforming (Ghaednia et al , 2020). The TA is in the inner bending arc (Zhu et al , 2007).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The material is elastic-perfectly plastic material, so there is no strain hardening while deforming (Ghaednia et al , 2020).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…They concluded that a single synthetic measure of initial particle deformation relative to deformation at first yield is insufficient to characterize the unloading response at large displacements when considering both stiffness and nonlinearity results. Ghaednia et al presented new formulations for single asperity frictionless indentation contact [ 44 ] and flattening contact [ 45 ] considering the effect of bilinear strain hardening. The deformations on both of the objects, real contact radius and contact force have been considered in the model.…”
Section: Introductionmentioning
confidence: 99%
“…They also presented a formula for calculating F/F c and A/A c in the elastic-plastic range. Recently, Gheadnia et al [45][46][47] analyzed elastic-plastic contact behavior between the deformable hemisphere and the flat using FEM by controlling the yield strength ratio between hemisphere and flat (Y 1 /Y 2 ). They demonstrated that the elastic-plastic contact behavior is related to the Y 1 /Y 2 ratio.…”
Section: Introductionmentioning
confidence: 99%